Helicobacter pylori CagA and IL-1β Promote the Epithelial-to-Mesenchymal Transition in a Nontransformed Epithelial Cell Model - Haruki Arévalo-Romero; Isaura Meza; Gabriela Vallejo-Flores; Ezequiel M. Fuentes-Pananá (Gastroenterology Research and Practice)
Gastric cancer is the third cause of cancer death worldwide and infection by Helicobacter pylori (H. pylori) is considered the most important risk factor, mainly by the activity of its virulence factor CagA. H. pylori/CagA-induced chronic inflammation triggers a series of gastric lesions of increased severity, starting with gastritis and ending with cancer. IL-1β has been associated with tumor development and invasiveness in different types of cancer, including gastric cancer. Currently, it is not clear if there is an association between CagA and IL-1β at a cellular level. In this study, we analyzed the effects of IL-1β and CagA on MCF-10A nontransformed cells. We found evidence that both CagA and IL-1β trigger the initiation of the epithelial-to-mesenchymal transition characterized by β-catenin nuclear translocation, increased expression of Snail1 and ZEB1, downregulation of CDH1, and morphological changes during MCF-10A acini formation. However, only CagA induced MMP9 activity and cell invasion. Our data support that IL-1β and CagA target the β-catenin pathway, with CagA leading to acquisition of a stage related to aggressive tumors.